2010
DOI: 10.5114/aoms.2010.17097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of compression stockings and layer compression systems in venous ulceration treatment

Abstract: IntroductionThe aim of the research was to compare the dynamics of venous ulcer healing when treated with the use of compression stockings as well as original two- and four-layer bandage systems.Material and methodsA group of 46 patients suffering from venous ulcers was studied. This group consisted of 36 (78.3%) women and 10 (21.70%) men aged between 41 and 88 years (the average age was 66.6 years and the median was 67). Patients were randomized into three groups, for treatment with the ProGuide two-layer sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Briefly, several authors reported that differences in the HRs are explained by the vast heterogeneity in the baselines due to the inclusion of ulcers with different sizes and of different duration [18, 19]. Our results confirm the above reports and show that the inclusion of ulcers of different sizes (large and short) and ulcers of different durations (short and long) contribute to severe heterogeneity in the baselines and differences in the HR among the reviewed bandages of four-LB, SSB compression, two-L SSB, four-L LSB, two-L LSB, and KTwo [12, 24, 27-30, 32, 34, 35, 42-44]. Again, this heterogeneity is still a significant limitation in the design of the current research, which needs to be addressed in future clinical studies.…”
Section: Discussionsupporting
confidence: 77%
“…Briefly, several authors reported that differences in the HRs are explained by the vast heterogeneity in the baselines due to the inclusion of ulcers with different sizes and of different duration [18, 19]. Our results confirm the above reports and show that the inclusion of ulcers of different sizes (large and short) and ulcers of different durations (short and long) contribute to severe heterogeneity in the baselines and differences in the HR among the reviewed bandages of four-LB, SSB compression, two-L SSB, four-L LSB, two-L LSB, and KTwo [12, 24, 27-30, 32, 34, 35, 42-44]. Again, this heterogeneity is still a significant limitation in the design of the current research, which needs to be addressed in future clinical studies.…”
Section: Discussionsupporting
confidence: 77%
“…However, factors like pain, drainage and difficulty in application limit its applicability [1]. Supplementary Table 5 shows a summary of studies evaluating compression techniques [69][70][71][72][73][74][75][76]. A Cochrane review revealed that compression increases ulcer healing rates; multicomponent and elastic bandage systems are more effective than single-component and inelastic bandage systems, respectively [77].…”
Section: Compression Therapymentioning
confidence: 99%
“…4 In another study conducted in an ulceration treatment clinic on a group of 46 patients with venous ulcers, the authors demonstrated a similar effectiveness of the 2and 4-layer system as well as compression stockings. 55 In yet another study, a group of 134 patients with wounds of venous etiology was randomly divided into 2 groups. 41 In one group, individually selected compression stockings were used, and in the other group, short-stretch bandages were applied to compare their effectiveness.…”
Section: Discussionmentioning
confidence: 99%